The Pharmacological Prospects of Curcuma: A Review of Its Antimicrobial, Antioxidant, and Anticancer Properties - Hossain, Farhad; Ashraful, ABM; Hossain, Md Jamal; Rashid, Mohammad A; Alam, AHM Khurshid (Dhaka University Journal of Pharmaceutical Sciences, 2025)
Cancer stands as a global threat nowadays, and its impact is becoming worse, affecting millions and causing high mortality rates due to drug resistance, improper treatments, and a lack of early detection. Despite advances in therapy, cancer treatment continues to pose significant challenges, largely due to multidrug resistance, treatment inefficacy, and delayed diagnosis. While oxidative stress (OS) is widely recognized as a key driver of carcinogenesis, the role of microbial dysbiosis in cancer progression remains understudied despite its potential significance. Emerging evidence suggests that targeting microorganisms and OS with antibacterial agents and antioxidants could offer novel therapeutic avenues. Natural resources (fruits, vegetables, and plants), particularly the Curcuma genus with over 100 species, have traditionally been used for their antimicrobial, antioxidant, and anticancer properties for many years. This review critically evaluates the therapeutic potential of Curcuma’s bioactive compounds as natural anticancer agents, emphasizing the interconnected roles of antimicrobial and antioxidant activities in modulating cancer progression. Our evaluation underscores Curcuma’s potential as an emerging alternative in cancer treatment, connecting its antimicrobial and antioxidant effects with its role in inhibiting cancer progression. Dhaka Univ. J. Pharm. Sci. 24(2): 231-249. 2025 (December)